1984
DOI: 10.1073/pnas.81.15.4642
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-factor-directed synthesis and secretion of mature foreign proteins in Saccharomyces cerevisiae.

Abstract: Saccharomyces cerevisiae cells were transformed with plasmids containing hybrid genes in which the sequence encoding mature human epidermal growth factor was joined to sequences encoding the leader region (preprosegment) of the precursor of the yeast mating pheromone afactor. These cells accurately process the hybrid protein and efficiently secrete authentic biologically active human epidermal growth factor into the medium. Previous studies on the expression of B-lactamase-proinsulin gene fusions in Escherichi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
202
0
2

Year Published

1986
1986
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 415 publications
(208 citation statements)
references
References 27 publications
4
202
0
2
Order By: Relevance
“…Both constructs contained a Myc epitope tag followed by a hexahistidine sequence at the C terminus (Myc-His) but differed in the presence or absence of a Glu-Ala-Glu-Ala sequence following an amino-terminal ␣ factor signal sequence. This Glu-Ala repeat may promote more efficient signal sequence cleavage under certain circumstances (29). After pilot experiments, we chose to use the construct lacking the Glu-Ala repeat for subsequent protein production, because expression levels from both constructs were similar, but N-terminal sequence analysis (data not shown) revealed that the Glu-Ala repeat was retained.…”
Section: Resultsmentioning
confidence: 99%
“…Both constructs contained a Myc epitope tag followed by a hexahistidine sequence at the C terminus (Myc-His) but differed in the presence or absence of a Glu-Ala-Glu-Ala sequence following an amino-terminal ␣ factor signal sequence. This Glu-Ala repeat may promote more efficient signal sequence cleavage under certain circumstances (29). After pilot experiments, we chose to use the construct lacking the Glu-Ala repeat for subsequent protein production, because expression levels from both constructs were similar, but N-terminal sequence analysis (data not shown) revealed that the Glu-Ala repeat was retained.…”
Section: Resultsmentioning
confidence: 99%
“…The yeast expression system of a random peptide library (Brake et al, 1984) seemed particularly suitable for this study; in this method, peptides are secreted into the culture medium and are therefore directly accessible to the antibody without solubilization of the cells. Furthermore, Klepfer et al (1993) demonstrated that yeast was able to translate the rabies virus G gene as a 68 kDa protein immunoreactive not only with a polyclonal antiserum but also with three neutralizing MAbs that were known to react only with native protein, indicating that the yeast was probably able to efficiently process this protein.…”
Section: Introductionmentioning
confidence: 99%
“…6,1986 on May 10, 2018 by guest http://mcb.asm.org/ Downloaded from independent of the other side of the junction for this particular secretory system. Further experiments may elucidate these possibilities.…”
Section: Discussionmentioning
confidence: 94%
“…Recently there have been several reports of secretion of heterologous protein products by using the a-factor gene of yeast cells (4,6,26). These systems result in proper processing of heterologous proteins during the secretion process.…”
Section: Discussionmentioning
confidence: 99%